Soldiers Three - Part 2 - Kipling, Rudyard, 1865-1936 (Salt Lake City, UT : Project Gutenberg, 2000)
"Soldiers Three - Part 2" by Rudyard Kipling is a collection of short stories published in 1899. This expanded edition combines three previously separate collections from 1888, featuring the adventures of British soldiers Learoyd, Mulvaney, and Ortheris in Afghanistan. The stories reveal the raw reality of military life during the British Empire's twilight, as common soldiers comment on their superiors and confront the brutal truths of war in central Asia. The collection also includes dramatic tales and stories exploring native Indian perspectives. (This is an automatically generated summary.)
"Love-o'-Women" -- The big drunk draf' -- The mutiny of the Mavericks -- The man who was -- Only a subaltern -- In the matter of a private -- The lost legion -- The drums of the fore and aft -- Judson and the Empire -- A conference of the powers.
Wikipedia page about this book: https://en.wikipedia.org/wiki/Soldiers_Three
Release date is 2000-06-01
Produced by Bill Stoddard and David Widger
Keywords: Soldiers -- Fiction; Short stories, English